Possibilistic model for aggregated search in XML documents. (1st January 2012) - Bessai-Mechmache, Fatma Zohra; Alimazighi, Zaia
In this paper, we are interested in content-oriented XML information retrieval which aims to retrieve not a set of relevant documents but a number of elements (parts of document) relevant to a query. Our goal is to revisit the granularity of the unit to be returned. More precisely, instead of returning the whole document or a list of disjoint elements of a document, as it is usually done in the most XML information retrieval systems, we attempt to build the best elements aggregation (set of non-redundant elements) which is likely to be relevant to a query composed of key words. Our approach is based on possibilistic networks. The network structure provides a natural representation of links between a document, its elements and its content, and allows an automatic selection of a combination of independent elements (i.e., set of non-redundant elements from different parts of the document tree) that better answers the user's query. Experiments carried out on a sub-collection of INEX INitiative for the evaluation of XML (INEX) retrieval, showed the effectiveness of the approach.